Women in employment: a feminist perspective / Fasihah Mohamad Shariff, Nur Liyana Aziz and Nur Azzureen Nor Hisham - Mohamad Shariff, Fasihah; Aziz, Nur Liyana; Nor Hisham, Nur Azzureen (2012)
The topic for our research is Women in Employment: A Feminist Perspective. From the topic itself, it can be inferred that two major things that is important for this research is feminism and employment. In this research, we seek to analyze the acceptance of feminist legal theory in Malaysia and also the issues regarding women's right in employment. This research is theoretical in nature as we do not conduct any interviews. It is a solely library-based research. Nowadays, women's capabilities have been acknowledged in most occupations. However, the legislation fails to provide sufficient protection for women's right. Therefore, our research is to review the theories of feminism and it relations with women's right in employment. We also analyze both international and domestic law which governed employment in Malaysia. The general idea is to prevent discrimination against women on the ground of gender basis.